2015
DOI: 10.4103/1119-3077.151035
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B virus infection in Nigeria, 2000-2013: A systematic review and meta-analysis

Abstract: Vaccination against the hepatitis B virus (HBV) in the West African nation of Nigeria is lower than many Sub-Saharan African countries. In Nigeria, HBV is reported to be the most common cause of liver disease. However, the extent of HBV exposure among Nigerians at average risk is unknown. Our aim, therefore, was to accurately estimate the HBV prevalence for the country and the prevalence for specific subgroups. We used electronic databases to select systematic reviews and meta-analyses from 2000 to 2013. Forty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
169
11
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(222 citation statements)
references
References 33 publications
17
169
11
2
Order By: Relevance
“…This study found a prevalence of HBV, 6.8%, which is close to Batina [4], Kisangani, and all by Baleka [5] Kinshasa and Koné and all [6] in Mali. The highest values were obtained in the meta analysis Nigerian Musa and all who found a value of 14% of voluntary blood donors [7] in the study and all Tanko Ghana [8], that of Cameroon made by Noah Noah [9], and all of Viet in Vietnam [10]. Lower prevalences were found; 4.68% in the Ivory Coast by N'DriN'Guessan [11], 3.21% in Madagascar by Rakotoniaina In India in the study and all Bamanahali in Karnataka, which had 2.12% [12], Secunderabad in that of Sukruthra 2009 and all that gives 1.28% [13], Pakistan, Syed Mukhtar was 1.97% [14], Congo in Kamina in the study of Kabamba and Kabila with 1.6% [15] Bukavu and that of 3.7% made by all and Namululi [16].…”
Section: Discussionmentioning
confidence: 72%
“…This study found a prevalence of HBV, 6.8%, which is close to Batina [4], Kisangani, and all by Baleka [5] Kinshasa and Koné and all [6] in Mali. The highest values were obtained in the meta analysis Nigerian Musa and all who found a value of 14% of voluntary blood donors [7] in the study and all Tanko Ghana [8], that of Cameroon made by Noah Noah [9], and all of Viet in Vietnam [10]. Lower prevalences were found; 4.68% in the Ivory Coast by N'DriN'Guessan [11], 3.21% in Madagascar by Rakotoniaina In India in the study and all Bamanahali in Karnataka, which had 2.12% [12], Secunderabad in that of Sukruthra 2009 and all that gives 1.28% [13], Pakistan, Syed Mukhtar was 1.97% [14], Congo in Kamina in the study of Kabamba and Kabila with 1.6% [15] Bukavu and that of 3.7% made by all and Namululi [16].…”
Section: Discussionmentioning
confidence: 72%
“…However, it is lower than the national average of 13.6%. [18] The higher national prevalence estimate may be modelled on higher rates from other parts of the country. Again, most studies on HBV prevalence in Nigeria are conducted among high-risk groups such as blood donors and patients with liver disease, which may lead to overestimation of rates.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Most prevalence data on HBV and HCV in Nigeria are hospital based, among cohorts of either patients with liver disease or blood donors. [11,18] The same applies to data on HIV prevalence in Nigeria, which have largely been derived from sentinel studies among pregnant women and other people presenting for care in health facilities. [19,20] It is vital to acquire population-based data on the prevalence of these blood-borne viruses to inform optimal national control strategies.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 The United Nations Children's Fund (UNICEF) and the World Health Organization (WHO) estimated that only 41% of Nigerians were vaccinated against HBV in 2013. 8 As reviewed by Musa et al, 9 the risk of contracting HBV in Nigeria is substantial, given a low vaccination rates coupled with the fact that as many as 75% of the population will be exposed. 10 There are reports of varying national and risk group-specific estimates.…”
Section: Introductionmentioning
confidence: 99%